First signs of reverse cardiac remodeling following one-month, low dose add-on sacubitril-valsartan therapy in patients with advanced systolic heart failure (Journal of Medical Science, 2022)
We investigated the early effects of low dose sacubitril/valsartan (S/V) on cardiac reverse remodeling (CRR). Methods: In 37 patients (45- excluded 8pts,mean age 64.5±17.5 years, five females), 24/26 mg S/V BID was started, and the second evaluation was performed after month. Results: Following CRR parameters improved: LVEDD (-∆2,9±2.6 mm; Student’s t-test: p =0.0098), LVESD (-∆2,4±2.5 mm; Student’s t-test: p=0.0092), LVEDV (-∆14.6±33.1 mL; Wilcoxon test: p = 0.0412), LVESV (-∆13.4±30.6 mL; Wilcoxon test: p =0.0442), LAVI (-∆8.7±37.7 mL/m2; Wilcoxon test: p = 0.0012), and EROA (-∆0.09±0.01 cm2; Student’s t-test: p = 0.0318). In opposite to LVEF, global longitudinal strain (GLS) changed from -6.6% to -7.9% (absolute improvement of 16%, Wilcoxon test: p=0.0013). Other parameters improving: 6-MWT (+∆65.4±75.8 m; Wilcoxon test: p = 0.0013) and the quality of life (MLHFQ 22 vs 16 scores; Student’s t-test: p= 0.0098), NT-pro BNP (-∆1203.1±3121.4 pg/mL; Student’s t-test: p = 0.0348) and troponin T (-∆ 4.7±9.4 pg/mL, Wilcoxon test: p = 0.0041). Correlation between GLS and LVESV (Pearson’s correlation coefficient: r = -0,4596, p = 0.0239) was found. ROC curve analysis showed that in the group with severe systolic dysfunction (GLS< -8%) clinical improvement (6MWT: AUC = 0.692, p = 0.0383) and CRR (MRvol: AUC = 0.736, p = 0.0062; LAVI: AUC = 0.710, p = 0.0414) are more likely to occur. Conclusions: Low-dose (24/26 mg BID) S/V therapy initiates CRR. S/V should be started in patients with less impaired LV systolic function (GLS < -8%) because CRR and clinical improvement are more likely to develop.